Intelligent animation programme: dynamic simulation of complex movements of four-legged animal based on machine intelligent and adaptive control theory - Wong, Kok Cheong (2008)
The aim of this project is to develop an effective animation system for facilitating the process of generating realistic quadruped locomotion under various working conditions and environments.